Praealpine Spruce (Picea Abies) Forest Dynamics During the Current Post-Little Ice Age Climate Era: A Case in the Swedish Scandes - Kullman, Leif (European Journal of Applied Sciences, 2022)
This study focuses on structural change of a praealpine stand of Norway spruce (Picea abies), in a context of centennial climate warming, in the Swedish Scandes. Progressive stand building followed on the discontinuation of the Little Ice Age by the late 19th century. A distinct hiatus of this process occurred during the 1980s, as a consequence of exceptionally cold winters with a sparse snow cover, particularly 1886/87. Extensive defoliation, caused by frost desiccation and fine root mortality, followed and culminated 1994 and 1995. Subsequently, climate warming resumed and stand foliation increased steadily up to the present day, when the forest appears equally healthy as prior to the 1980s. Hereby, recent spruce stand evolution adds to current progressive climate-mediated restructuring of upper montane forests.